Pengaruh Likuiditas, Profitabilitas, Kebijakan Utang dan Pertumbuhan Penjualan terhadap Penghindaran Pajak - Syarifah Muthmainah; Hermanto Hermanto (Universitas Batanghari, 2023)
The purpose of this study is to determine the determinants of tax avoidance such as liquidity, profitability, leverage and sales growth. This study utilizes information taken from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange using a purposive sampling test method that meets the research criteria. The research period was taken for 6 years with a total of 330 data from 55 entities in the manufacturing sector. This study utilizes multiple linear analysis methods with secondary data types. The results of the study show that there is a simultaneous influence between liquidity, profitability, debt policy and sales growth on tax avoidance, there is no relationship between liquidity and tax avoidance, there is a negative relationship between profitability and tax avoidance, there is a positive relationship between debt policy and tax avoidance. positive sales growth on tax avoidance.